A novel method for dust mitigation from PV cell surfaces. (1st September 2021) - Yilbas, Bekir Sami; Abubakar, Abba Abdulhamid; Al-Qahtani, Hussain; Mohammed, Anwaruddin Siddiqui; Al-Sharafi, Abdullah
Highlights: A new method of dust mitigation from PV panel surfaces is proposed. Water droplets roll over hydrophobic meshes while mitigating dust particles. Mesh open screen size remains important for selected size of water droplet to roll. Water infusion on dust particle surfaces enables droplets to pick up dust from PV surfaces. Abstract: A novel method is introduced eliminating dust from PV cells by rolling droplets. Since hydrophobizing of PV cell surfaces reduces the optical transmittance, hydrophobized meshes are adopted laying over PV cell surfaces towards reducing the coverage area of hydrophobized coating over cell surfaces. Droplet rolling and droplet fluid spreading conditions on PV cell surfaces are evaluated and the mesh size resulting in droplet rolling over the PV cell surface is incorporated in the experiments. Droplet dynamics over the hydrophobic mesh laid dusty PV cell surfaces are examined incorporating the high-speed recorded data. Findings reveal that rolling droplets mitigate dust from hydrophobic mesh-laid PV cells surfaces without leaving droplet fluid residues on PV cell surfaces. During dust mitigation, droplet fluid interacts with dust via infusion, which slightly reduces the translational velocity of the rolling droplet. PV cell output reduction becomes less (almost 11%) for the hydrophobic mesh laid surface than that of hydrophobized cell surfaces after dust removal by rolling droplets.